Basic VLC Infrastructure Design Using Two Color Diffuse LED as Receiver and Color Intensity Modulation - Herti Miawarni (Fakultas Teknik Universitas Bhayangkara, 2016)
VLC technology continuously developed until now. Development ranging from modulation system, basic infrastructure, up to complex networks. In this research conducted an experiment in terms of basic infrastructure which Diffuse LED is used as the main component on VLC receiver. The purpose of this research is to design and then analyze in an effort to build the basic infrastructure of VLC. Experiment performed on a simple modulation system for easy analysis process. For more simplicity, Color Intensity Modulation using only two colors: red and blue to present the logic high and low. From trials that have been done, Diffuse LED that used as the main component in the Receiver Unit has performed well in the period of the signal greater than or equal to 20 uS. In these conditions, BER reaches 0%. So in other words the shortest period of signal reaches a maximum of 20 uS and maximum bit rate of 100 Kbps. And then observations using the oscilloscope showed that in the same signal period, information signal shape that has been received are similar with the shape of signal that has been sent. Overall results, VLC system that has been designed and analyzed suitable for low bit rate communication.